Inhibitory activity of limonoids from Khaya grandifoliola C.DC (Meliaceae) against hepatitis C virus infection in vitro - Kouam Arnaud; Njayou Frédéric Nico; Yuan Fei; Babayemi Oladejo; He Hongtao; Mkounga Pierre; Moundipa Paul (Mashhad University of Medical Sciences, 2021)
Objective: A fraction from Khaya grandifoliola has recently been shown to inhibit hepatitis C virus (HCV) infection and three limonoids (17-epi-methyl-6-hydroxylangolensate, 7-deacetoxy-7-oxogedunin and 7-deacetoxy-7R-hydroxygedunin) were purified from this fraction. The present study aimed at assessing the inhibitory effect of these limonoids on HCV using cell-culture derived HCV (HCVcc) system. Materials and Methods: Cytotoxic effects of the limonoids on Huh7.5 cells were assessed by MTT assay. Huh7.5 cells were transfected with RNA transcripts of the plasmid Jc1/GLuc2a, carrying a Gaussia luciferase reporter gene to rescue the HCVcc particles which were used to infect naïve cells in the presence or absence of the studied limonoids during 72 hr. Infection and replication rates were monitored by luciferase reporter assay and immunofluorescence assay (IFA) while cellular gene expression was analyzed by western blot, respectively. Results: The limonoids inhibited HCV infection mostly by targeting entry and replication stage. Their inhibitory effect on entry step, comparable to that of anti-CD81 antibody, was related to the blocking of CD81 receptor. In the replication step, the limonoids decreased the expression of NS5B similar to danoprevir. These compounds also significantly decreased but up-regulated the expression of Class-III phosphatidylinositol 4-kinase alpha and 2',5'-oligoadenylate synthase-3, respectively. Conclusion: The present findings suggest that limonoids from K. grandifoliola are potential anti-HCV agents and may offer an advantage in the treatment of HCV infection.